148 Paediatric cardiac arrest: is there any myocardial damage in paediatric patients when adult defibrillation energies are administered?. (5th June 2017) - Davis, Laura; Funston, Rebecca; Crawford, Paul; McAlister, Olibhar; McCartney, Ben; Torney, Hannah; Courtney, Alistair; Gregson, Rachael; McEneaney, David; Clutton, Eddie; Adgey, Jennifer
Abstract : Purpose: When attempting defibrillation in an out-of-hospital paediatric patient, the use of a reduced energy is currently recommended in the resuscitation guidelines due to concerns surrounding potential myocardial damage. The purpose of this pilot study was to investigate the 1st shock success of two different automated external defibrillator (AED) energy protocols and observe the resulting levels of myocardial damage in a paediatric model of cardiac arrest. Method: A total of six piglets (10–25 kg) were anaesthetised, instrumented and ventricular fibrillation (VF) was electrically induced. After approximately 15 s of untreated VF, a defibrillation shock was delivered using the selected device in line with Protocol A (adult energy doses of 150J) or Protocol B (paediatric energy doses of 75J). Following successful defibrillation, a 3 min recovery period was allowed for the heart to recover before VF was again induced with a maximum of 20 shocks administered. Blood samples were collected at pre-defined time-points whilst the animal was under anaesthesia and analysed for cardiac troponin I (cTnI). After the defibrillation phase of the protocol, the animals remained anaesthetised and vital signs monitored for a period of 6 hours with blood samples collected hourly for further analysis. Results: A total of 120 shocks were delivered across both protocols with a 100% shockable rhythm detection and 100% first shock success observed in both Protocol A and B. Prior to the induction of VF, Protocol A and B presented with similar initial mean (±SD) levels of cTnI; 0.04 (±0.03) ng/ml (n=3) and 0.03 (±0.02) ng/ml (n=3), respectively. Comparable results of cTnI were also observed upon completion of the defibrillation phase (Shock 20); Protocol A – 0.12 (±0.05) ng/ml and Protocol B – 0.14 (±0.07) ng/ml. An increase in mean cTnI was detected into the rest period, peaking by 5 hours for both energy protocols. At the 6 hour endpoint of this study, the mean value of cTnI in the blood was reducing for both energy protocols with no statistically significant difference observed between the high and low defibrillation energy groups. Conclusion: There was no statistical evidence to suggest that treating the paediatric animals with a higher adult shock energy caused more myocardial damage than a paediatric shock energy. Further investigations are warranted to determine the long term impact on myocardial tissues in a paediatric patient.